Swarm Intelligence: Revolutionizing Drone Technology Through Collective Behavior - Shruti Goel, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of swarm intelligence on drone technology, highlighting how principles derived from nature's collective systems enable unprecedented capabilities in unmanned aerial operations. By adopting decentralized decision-making architectures inspired by ant colonies and bird flocks, drone swarms achieve superior resilience, adaptability, and scalability compared to traditional centralized control paradigms. The implementation of bio-inspired algorithms—including Ant Colony Optimization, Particle Swarm Optimization, and reinforcement learning techniques—facilitates emergent collective behaviors that dynamically respond to changing environments without explicit programming. These systems demonstrate remarkable advantages across diverse applications, from search and rescue operations to environmental monitoring, military reconnaissance, disaster management, precision agriculture, and infrastructure inspection. Despite current challenges in real-time communication, energy optimization, heterogeneous coordination, security, and human-swarm interaction, the integration of artificial intelligence with collective intelligence mechanisms continues to advance drone capabilities toward increasingly autonomous operation in complex environments.
Keywords: Swarm Intelligence; Decentralized Coordination; Bio-inspired Algorithms; Emergent Behavior; Autonomous Drones